(untitled) (Bangladesh Journal of Medical Microbiology, 2016)
A total of 45 clinically suspected cases of meningitis of all ages, admitted at Rajshahi Medical College Hospital(RMCH), were studied to find out the etiological agents of meningitis. Among the cases, 32 (7l.1oh) were diagnosed asaseptic meningitis and L3 (ZS.Sgoh) as bacterial meningitis by the conventional CSF study. But out of total 45 cases,lg (40oh) were diagnosed as bacterial meningitis by Latex particle agglutination test (LPAT). The LPAT is widelyused in clinical microbiology laboratories and can be considered as an important supplement to the culture andGram stain of CSF specimens. Rapid antigen detection tests may provide positive results when culture and Gramstain results are negative for meningitis patients who have received antimicrobial therapy. So, in our country, where empirical broad-spectrum antibiotic is randomly used, LPAT may be considered as an adjunct to establish thediagnosis of bacterial meningitis. Bangladesh J Med Microbiol 2007;01(01):10-12